Effect of Mn promoter on Rh/tungsten carbide on product distributions of alcohols and hydrocarbons by CO hydrogenation - Won, Ba Da; Ham, Hyeongwon; Cho, Jae Min; Lee, Jong-Bae; Kim, Chul-Ung; Roh, Hyun-Seog; Moon, Dong Ju; Bae, Jong Wook (ROYAL SOC CHEMISTRY, 2016)
Roles of Mn promoter on Rh-impregnated mesoporous tungsten carbides (WxC) have been investigated for direct synthesis of mixed alcohols by CO hydrogenation of syngas. Mn/Rh ratio on the mesoporous WxC, prepared using a hard-template of mesoporous SBA-15, significantly altered CO conversion and product distributions. An optimal Mn content of 3 wt% on Rh/WxC was responsible for a high CO conversion of 8.1% and selectivity for higher alcohols of 54.4% compared with other catalysts. The enhanced activity and selectivity towards alcohols at an optimal Mn content were mainly attributed to close interaction of Rh and Mn nanoparticles with partially reduced Rh nanoparticles on the WxC, which enhanced CO adsorption as well as suppressed CO hydrogenation to produce light hydrocarbons. This superior activity originated from a higher dispersion of Rh nanoparticles, which intimately interacted with Mn species, maintaining an appropriate surface ratio of metallic Rh to oxidized Rh+ surfaces. The structures of the ordered mesoporous WxC support greatly altered the chemical states of Rh nanoparticles by generating a strong metal-support interaction as well, and Rh-Mn(3)/WxC showed a high production rate of higher alcohols by synergistic effects of the supported Rh-Mn nanoparticles with an appropriate interaction with the mesoporous WxC support.
Keywords: RH-BASED CATALYSTS; TUNGSTEN CARBIDE; C-2-OXYGENATES SYNTHESIS; SYNGAS; ETHANOL; NANOPARTICLES; MANGANESE; PERFORMANCE; CONVERSION; MIXTURES